2022
DOI: 10.1021/acs.energyfuels.2c03053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poly(vinylpyrrolidone) on the Dynamic Viscosity of Methane Hydrate Systems at High-Pressure Driving Forces: Investigation of Concentration, Molecular Weight, and Shear Rate

Abstract: The viscosity of methane hydrate slurries with poly(vinylpyrrolidone) (PVP) at 700 and 7000 ppm by weight, molecular weights of 40 000 (PVP40) and 360 000 (PVP360) Da, and shear rates of 400 and 80 s–1 were measured in a high-pressure rheometer with pressures up to 30 MPag and compared to pure water systems. The additives successfully reduced the formation of high-viscosity slurries but at low concentrations were incapable of delaying hydrate agglomeration at the late growth stage. The average relative time re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…A direct comparison was made between the viscosity of hydrate slurries with and without polymer additives. The increase in viscosity of aqueous solutions due to dissolved KHIs was considered to be negligible for the concentrations selected for this study, since a previous study has shown that the viscosity difference between pure water and aqueous solutions with 7000 ppm of PVP was in the order of 10 –1 mPa·s for temperatures between 0 and 10 °C and for pressures between 0 and 5 MPag …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A direct comparison was made between the viscosity of hydrate slurries with and without polymer additives. The increase in viscosity of aqueous solutions due to dissolved KHIs was considered to be negligible for the concentrations selected for this study, since a previous study has shown that the viscosity difference between pure water and aqueous solutions with 7000 ppm of PVP was in the order of 10 –1 mPa·s for temperatures between 0 and 10 °C and for pressures between 0 and 5 MPag …”
Section: Resultsmentioning
confidence: 99%
“…Median time required for methane hydrate slurries to reach 200 mPa·s for Left: PVP40 700 ppm (data from Du et al, 2022) and Right: PS4- b -PVP40 700 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations